Patients’ satisfaction and prevalence of complications on surgical extraction of third molar - Lee, Crystal TY (Patient Prefer Adherence, 2015)
OBJECTIVES: To study patients’ satisfaction and prevalence of complications in surgical extraction of impacted third molar by senior dentists and recently graduated dentists in a university dental clinic. METHOD: Patients who had impacted third molar extraction in a university dental clinic by two associate dentists who had <2 years of experience and two senior dentists who had >15 years of experience were evaluated in this study. Patients’ age, sex, history of pericoronitis, tooth extracted, and radiographic assessment of the impacted tooth were recorded. Immediately after suture removal, the patients were invited to indicate their satisfaction on a Likert scale of 1–5. RESULTS: A total of 546 patients received extraction, and 251 patients were operated by associate dentists. Patient satisfaction was higher among those who had noncomplicated surgery (P=0.007), short treatment time (P<0.001), and had no postsurgical emergency appointments (P<0.001). The prevalence of seeking postsurgical emergency appointments was 9.2%. The reasons were severe pain (4.8%), swelling (2.6%), bleeding (2.4%), alveolar osteitis (0.9%), paresthesia (0.9), and trismus (0.5%). The prevalence of postsurgical complication(s) in associate dentists and senior dentists was 11.6% and 7.1%, respectively (P=0.050). The mean satisfaction scores for associate dentists and senior dentists were 4.17 and 3.95, respectively (P=0.002). CONCLUSION: Although a higher rate of postsurgical complications was observed among the patients treated by the recently graduated dentists, their patients’ satisfaction scores were higher than that of the senior dentists. Around 9% of patients attended postsurgical emergency appointments, and their common reason was severe pain.